(untitled) (Research, Society and Development, 2020)
The suitability of the spatial arrangement of soybean is a tool capable of promoting better use of the agricultural environment, allowing the crop to express its yield potential. Therefore, the aim of this study was to evaluate different implementation systems with and without an increase in the plant population of soybean with indeterminate growth habit variety cultivated in the Brazilian Cerrado. The experiments were performed in the 2013/14 and 2014/15 seasons in Rio Verde, Goias state. The experimental design was randomized blocks with four replication in a 4x2 factorial scheme. The treatments presents four implementation systems (traditional, reduced, double rows and crossed) associated with two populations of BMX Potência RR® (recommended and increased by 33%) with presented indeterminate growth habit. The results indicate that the reduced system has an adoption potential for soybean with indeterminate growth habit. The increase in the plant population in the 2013/2014 season, increased 20% of soybean yield in relation to the recommended population, proving to be a promising technique since it considerate the costs involved.